????? ????? ????? ??????? ? ??? ?????? ?????? ?????? ????? - Majidatun Ahmala (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
Arabic in Indonesia is not only the language of religion, inheritance and civilization but also the language of communication between Arabic instructors or between Arabic students. In addition, Arabic is also daily language used in boarding schools that are scattered throught the regions in Indonesia. Arabic always develops according to the times. So, all Arabic instructors must also improve their competence. Madrasah Al-Sun education institutions seemed to be a solution for all Arabic language teachers in Indonesia, because the Madrasah Al-Sun used a special strategy in its teaching, namely Uslub Al-Sun. By using Uslub Al-Sun, the instructor is able to learn more deeply about Islamic civilization and is able to master contemporary vocabulary due to active discussions conducted. This study uses qualitative methods so that researchers get more in-depth data in accordance with the facts in the foeld about Uslub Al-Sun that is used to improve the teaching competence of Arabic.